Response of endophytic Biscogniauxia mediterranea to variation in leaf water potential of Quercus cerris - Vannini, A. (2009)
Endophytic behaviour of Biscogniauxia mediterranea, the causal agent of charcoal disease of oak, was studied over two growing seasons on Quercus cerris in a forest in central Italy. Isolation of the fungus from asymptomatic tissues varied with tissue type, period of sampling and year. Presence of the fungus in asymptomatic plants was significantly higher in fall, compared with that in spring and summer. However, a significant effect of tissue water content on the presence of B. mediterranea was recognized. The results suggest that proliferation of B. mediterranea is favoured during the endophytic phase by a decrease in host water potential.